2015
DOI: 10.1159/000442584
|View full text |Cite
|
Sign up to set email alerts
|

Missed Diagnosis of an Intraorbital Foreign Body of Homemade Fireworks Origin: A Case Report

Abstract: Purpose: We report a rare case of traumatic injury to the eye caused by homemade fireworks in a Chinese juvenile patient with a metal ring left in the orbit after having been sutured at the Emergency Department. Methods: An 11-year-old boy presented with a traumatic injury to the right eye from homemade fireworks. Following initial assessment involving maxillofacial computed tomography (CT) and suturing at the Emergency Department, he was transferred to our department for further evaluation because of his poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…1 Yet, we have identified only 24 unique cases of fireworks injuries in the head and neck with CT imaging described in the literature with only 4 case series. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Here, we presented 18 additional cases that demonstrated a wide range of CT findings, including soft tissue swelling and Previous studies have also demonstrated that fireworks injuries disproportionately affect children, young adults, and males, 1-3 which is consistent with findings from our series of cases. Furthermore, the 24 cases in the literature showed a variety of CT findings: 13 cases with skull/maxillofacial fractures, 13,[15][16][17]20,25 7 cases with globe rupture, 9,12,16,20 10 cases with foreign bodies, 9,11,14,15,[18][19][20][21][22][23] 11 cases with intracranial hemorrhage or hematoma, 8,10,11,13,16,17,…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…1 Yet, we have identified only 24 unique cases of fireworks injuries in the head and neck with CT imaging described in the literature with only 4 case series. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Here, we presented 18 additional cases that demonstrated a wide range of CT findings, including soft tissue swelling and Previous studies have also demonstrated that fireworks injuries disproportionately affect children, young adults, and males, 1-3 which is consistent with findings from our series of cases. Furthermore, the 24 cases in the literature showed a variety of CT findings: 13 cases with skull/maxillofacial fractures, 13,[15][16][17]20,25 7 cases with globe rupture, 9,12,16,20 10 cases with foreign bodies, 9,11,14,15,[18][19][20][21][22][23] 11 cases with intracranial hemorrhage or hematoma, 8,10,11,13,16,17,…”
Section: Discussionsupporting
confidence: 85%
“…1 Yet, we have identified only 24 unique cases of fireworks injuries in the head and neck with CT imaging described in the literature with only 4 case series. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Here, we presented 18 additional cases that demonstrated a wide range of CT findings, including soft tissue swelling and emphysema; extensive skull fractures; ocular injuries, such as globe rupture; the presence of retained foreign bodies; and intracranial injuries, such as subdural and subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A computed tomography (CT) scan is considered the gold standard in imaging modality for metallic foreign bodies. 3 However, CT findings can vary. It is imperative to maintain a high index of suspicion in to avoid misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative to maintain a high index of suspicion in to avoid misdiagnosis. 3 To avoid missing the diagnosis, careful evaluation and detailed imaging of the globe and surrounding structures, including the brain and paranasal sinuses, is indicated.…”
Section: Introductionmentioning
confidence: 99%